METAMODERNISM MAN IN THE WORLDVIEW DIMENSION OF NEW CULTURAL PARADIGM - Y. O. Shabanova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The research is based on the comprehension of the anthropological tendencies of the metamodernism, which presupposes the consistent solution of the following tasks: a) explication of the content of post-postmodernism in modern philosophical literature; b) identification of the ideological basis of metamodernism anthropology; c) characteristics of the problem field of metamodernism anthropology and the state of man in the modern era. Theoretical basis. Anthropology of the metamodernism for the first time defines socio-cultural context through the hesitative state between the values of modernism and their rejection by the postmodernism, which makes it possible to formulate the peculiarity of the time as a desire to reconstruct a Holistic Man, impartial to the dominant worldview attitudes of a social nature. Anthropology of the metamodernism is presented as the individualization of the socio-cultural space in the form of human self-reconstruction at all anthropological levels. An era without an unambiguously expressed moral guideline is based on the ethics of all-acceptance, the only justification of which is the existence of a universal right to beingness. Digitalization as a process of digital transformation of society creates conditions for the value realization of the free choice of metamodernism man, through which a Holistic Man is accomplished. Originality. It is substantiated that metamodernism as a descriptive position of the modern cultural dominant of the digitalized era is characterized by a state of hesitation between the values of modernism and postmodernism. The anthropology of the metamodernism manifests itself in the form of the reconstruction of the holistic man and the self-reconstruction of the inner man. The peculiarities of the human metamodernism are recognized as the mutual complete determinability of the individual and the mass. Conclusions. Metamodernism is the formulation of the problem of a man in a new perspective: what to be and how to survive between the extremes of semantic poles, without losing dignity and unique intrinsic value. Proceeding from this, the fate of a metamodernism man is determined in pursuit of the endlessly receding horizons of the anthropology of incompleteness, which is carried out through post-irony, naive sincerity, optimistic openness to the world.